2022
DOI: 10.1038/s41598-022-20090-1
|View full text |Cite
|
Sign up to set email alerts
|

China’s LNG import risk assessment based on the perspective of global governance

Abstract: The uncertainty of LNG import risks will have a significant impact on China's energy security. This paper establishes a multi-agent game model based on the current LNG transportation network and global LNG supply and demand pattern, evaluates the LNG import risks faced by China under the global governance model, and simulates and predicts the optimal LNG import strategy of China in 2030. The research results show that between 2007 and 2020, China’s LNG import risks increased rapidly compared with political ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The fourth stand highlights studies on diversifying natural gas portfolios in response to the implications of natural gas market variabilities on energy security. In the literature, studies addressed the natural gas and LNG trade dynamics and the ability of suppliers to secure long-term contracts as an indicator of demand stability [ 22 , 24 , [98] , [99] , [100] ]. Given the considerable share of income obtained from energy commodities exports in national GDPs, demand turbulence significantly impacts national economies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The fourth stand highlights studies on diversifying natural gas portfolios in response to the implications of natural gas market variabilities on energy security. In the literature, studies addressed the natural gas and LNG trade dynamics and the ability of suppliers to secure long-term contracts as an indicator of demand stability [ 22 , 24 , [98] , [99] , [100] ]. Given the considerable share of income obtained from energy commodities exports in national GDPs, demand turbulence significantly impacts national economies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, significant research efforts have been recognised in the literature to assess and optimise the energy portfolios for import and domestic utilisation purposes [ [17] , [18] , [19] , [20] ]. Moreover, several studies reported analytical frameworks on the LNG importation portfolio to investigate the optimal strategies [ [21] , [22] , [23] , [24] ]. For producing companies, early market assessments facilitate deciding and planning production capacities, selling portfolios, and delivery plans [ [25] , [26] , [27] ].…”
Section: Introductionmentioning
confidence: 99%